ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI KERJA LANSIA DI KECAMATAN KUTA UTARA - Ni Putu Ayu Liana Waisnayanti; Ni Nyoman Yuliarmi (Universitas Udayana, 2023)
The purpose this study to analyze effect of education level, family income health and number of dependents simultaneously and partially on the work participation of the elderly in North Kuta District. This research was conducted in North Kuta district. Samples was 99 elderly people working in North Kuta District. Data were collected using observation methods, structured interviews and in-depth interviews with key informants whose results were analyzed using moderation regression analysis techniques. The results of the study concluded that the level of education, health, family income and the number of dependents simultaneously and partially affect the work participation of the elderly in North Kuta District. Partially health and family income have a negative effect on the work participation of the elderly in North Kuta District. Education level did not negatively affect the work participation of the elderly in North Kuta District and the number of dependents partially did not have a positive effect on the work participation of the elderly in North Kuta District. Keywords: Education, health, family income, number of dependents, work participation of the elderly and North Kuta District.